Efektivitas Adopsi Inovasi dalam Pembudidayaan Tanaman Melon: Sistematika Review - Lasma Rintan Antonia Pasaribu; Almeira Hadiningpraja; Chealse Aulia Puteri; Wien Kuntari (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Adoption of melon (Cucumis Melo L.) cultivation innovation plays an important role in increasing productivity and efficiency. This study discusses the application of innovation adoption in melon plants with greenhouse technology, hydroponics, modern irrigation technology, post-harvest processing mechanisms for breeding. This literature review uses the Systematic Literature Review (SLR) method to compare National Journals and International Journals that are relevant to Innovation Adoption. The use of the Internet of Things (IoT) allows automatic monitoring of environmental conditions. Technology in melon cultivation has a significant impact on agricultural productivity and efficiency. In the hydroponic system of soilless cultivation in limited land conditions, each innovation has challenges in its implementation, such as high investment costs, the need for training for farmers, and limited access to certain technologies